Cover Feature: Biomass‐based Hierarchical Porous Carbon for Supercapacitors: Effect of Aqueous and Organic Electrolytes on the Electrochemical Performance (ChemSusChem 23/2019). Issue 23 (26th November 2019) - Chen, Zhimin; Wang, Xiaofeng; Ding, Zhiyao; Wei, Qingling; Wang, Zichen; Yang, Xiaomin; Qiu, Jieshan
Abstract : The Cover Feature shows the process of transfer and adsorption of different electrolyte ions in the biomass‐based hierarchical porous carbon (SCPC) electrode for supercapacitors. The electrochemical performance of the SCPC electrode in various electrolytes is significantly different, which is mainly attributed to the difference in electrolyte ion size, ionic conductivity, matching between the electrolyte ions and pore structure, and matching between anions and cations adsorbed on the positive and negative electrodes, respectively. This work not only establishes the relationship between the structure of SCPC and its electrochemical performance in different electrolytes but also provides a valuable reference for the high value‐added utilization of SCPC. More information can be found in the Full Paper by Z. Chen et al. on page 5099 in Issue 23, 2019 (DOI: 10.1002/cssc.201902218 ).